Biodegradation of biodiesel/diesel blends by Candida viswanathii - Soares Junior, Jose [UNESP]; Mariano, Adriano Pinto [UNESP]; de Angelis, Dejanira de Franceschi [UNESP] (Academic Journals, 2009)
This work is aimed to assess the aerobic biodegradation of biodiesel/diesel blends (0, 2, 5, 20 and 100%, v/v) by Candida viswanathii. The biodegradation potential of the inoculum was assessed with the redox indicator 2,6-dichlorophenol indophenol (DCPIP) test and with respirometric experiment in biometer flasks (250 mL) used to measure the microbial CO(2) production. In the latter, the inoculum was added to a contaminated soil with the blends (addition of 50 mL of fuel/Kg of soil from a non-contaminated site). C. viswanathii was able to increase significantly (approximately 50% in terms of CO(2) production) the biodegradation in soil of biodiesel/diesel blends and neat biodiesel since it preferable biodegrades biodiesel. Without inoculum the biodegradation of diesel oil was higher than biodiesel and blends (47.3, 51.1, 5.7 and 22.1% in terms of CO(2) production by B2, B5, B20 and B100, respectively) presumably due to the presence of the antioxidant terc-butyl-hydroquinone (TBHQ) in the biodiesel.
Keywords: Diesel; biodiesel; blends; biodegradation; bioaugmentation; TBHQ